2019
DOI: 10.1016/j.sjbs.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal effects of Vernonanthura nebularum against two economically important pest insects

Abstract: Vernonanthura nebularum (Cabrera) H. Rob. (Asteraceae), an endemic species from the north of Argentina, is a rich source of elephantopus-type sesquiterpene lactones. These compounds have proved to be promising antiparasitic agents, but there is no report about their action against pest insects. In this work we studied for the first time the antifeedant and toxic effects of V. nebularum natural products against the fall army warm Spodoptera frugiperda Smi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…Plant extracts exerted negligible effects on nutritional parameters of adult weevils except for the highest dose of water extract that caused a significant reduction of food intake (RCR) and relative growth rate (RGR) when compared to control. Since no ingestion toxicity was observed this alteration in nutritional parameters indicates the presence of antifeedant constituents in the water extract (rather than post-ingestion toxicants) which more likely act on the gustatory organs of the mouthparts 38 . However, chemical analysis of water extract is needed to support or refute this hypothesis, as well as for better understanding the variability registered with this extract for the other nutritional indexes.…”
Section: Discussionmentioning
confidence: 95%
“…Plant extracts exerted negligible effects on nutritional parameters of adult weevils except for the highest dose of water extract that caused a significant reduction of food intake (RCR) and relative growth rate (RGR) when compared to control. Since no ingestion toxicity was observed this alteration in nutritional parameters indicates the presence of antifeedant constituents in the water extract (rather than post-ingestion toxicants) which more likely act on the gustatory organs of the mouthparts 38 . However, chemical analysis of water extract is needed to support or refute this hypothesis, as well as for better understanding the variability registered with this extract for the other nutritional indexes.…”
Section: Discussionmentioning
confidence: 95%
“…Topical application of Farnesol onto 5 th instar nymphs of the red cotton stainer Dysdercus koenigii led to the metamorphosis of adults with malformed wings (Kumar and Gupta, 2017). Sosa et al (2019) observed serious wing malformations in adults of S. frugiperda after larval treatments with some Sesquiterpene lactone compounds. Feeding of S. littoralis 2 nd instar larvae on plant leaves previously dipped in Nano-chitosansolution led to the production of deformed adult moths (Marouf, 2020).…”
Section: I33 Prolonged Oviposition Periodmentioning
confidence: 90%
“…Larval treatment with Pogostone (isolated as the main constituent of essential oil from Pogostemon cablin) resulted in some deformities in adult moths of S. litura and the beet armyworm Spodoptera exigua (Huang et al, 2014). Fraction II (300lg/g of diet) from Vernonanthura nebularum natural products was found the most active substance causing wing malformations in adults of the fall armyworm Spodoptera frugiperda (Sosa et al, 2019).…”
Section: Disrupted Adult Morphogenesismentioning
confidence: 99%